Evaluation of the effectiveness of integrated management and mating disruption in controlling gypsy moth Lymantria dispar (Lepidoptera: Lymantriidae) populations - GOODARZ HAJIZADEH; MOHAMMAD REZA KAVOSI (Smujo International, 2012)
Abstract. Hajizadeh G, Kavosi MR. 2012. Evaluation of the effectiveness of integrated management and mating disruption in controlling gypsy moth Lymantria dispar (Lepidoptera: Lymantriidae) populations. Nusantara Bioscience 4: 27-31. This study was conducted during 2008 and 2009 in Daland National Park (north of Iran) to compare the effectiveness of mechanical control used in combination with mating disruption (integrated management) and only mating disruption in controlling gypsy moth, Lymantria dispar (L.) (Lepidoptera: Lymantriidae). Male moths and egg mass counts were taken before (2008) and after (2009) the two treatments were applied. In sites with integrated management and with mating disruption only, 1,828 and 1,793 egg masses/tree, and 412.75 and 207.75 male moths/trap were observed, respectively. Both the numbers of egg masses/tree and of male moths/trap were significantly lower in sites with integrated management than in sites with only mating disruption. This study shows that integrated management was more effective than mating disruption in reducing infestation levels in the study site.